PENGARUH MEDIA PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMKN 71 JAKARTA - Rizky Alfariez; Nadiah Nadiah (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
There is a learning process at SMK Negeri 71 Jakarta that has not used learning media that is easy to understand and apply, one of the learning media that is easy to apply is Microsoft power point. This study aims to calculate and analyze how much influence learning media has on students' motivation at SMK Negeri 71 Jakarta. This research method is a correlation method. The sample of this study were 35 students, namely all students of class XI RPL 2. The data collection used a non-probability sampling technique. The results of the data analysis in this study used the product moment correlation formula, namely that there was an influence of learning media on students' critical thinking skills of 0.834 or 83.4% with an interpretation of moderate. Then the results of the correlation value significance test show positive and significant results by comparing r_xy and r tables of 5% and 1%. Based on this comparison, the results of the 5% and 1% r tables are 0.344 and 0.442. then r_xy ≥ r table 5% and 1% which means the null hypothesis or Ho is rejected and the alternative hypothesis or Ha is accepted and the results indicate that there is an influence of learning media on students' critical thinking skills